Analisis Kebijakan Merdeka Belajar terhadap Perkembangan Teknologi dan Informasi pada Kampus Merdeka - Putri, Nabila; Febriyenti, Dini; Rizandi, Hidayat; Trisoni, Ridwal (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2024)
This article discusses the application of the Independent Learning Policy Analysis to the Development of Technology and Information at Merdeka Campus. Merdeka Belajar Kampus (MBKM) is a newly established policy in Indonesia for higher education by utilising technological and information developments. This research uses the literature review method to extract information from primary and secondary data sources. The results showed that Merdeka Belajar-Kampus Merdeka is a policy of the Minister of Education and Culture which aims to encourage students to master various sciences to enter the world of work. The development of information technology makes it easy to communicate information exchange so that place, time and distance are no longer an obstacle. The rapid development of information technology cannot be separated from the development of computer techniques, learning media is not limited to letters and images but can be combined with gr aphics, animation, video, audio together so that this media is better known as multimedia. The positive effect of using the internet for education in building human resources in the world of education must be able to keep up with the development of science and technology applications. With the Independent Learning and Independent Campus Policy supported by the development of technology and information, it is hoped that it can encourage students to develop all their competencies, so that this can encourage the success of the education process in the education system in Indonesia. Keywords: Independent Learning, Information Technology, Independent